THE INFLUENCE OF MOTIVATION AND KNOWLEDGE ON THE COMPLETENESS OF MEDICAL RECORDS WITH ATTITUDE AS AN INTERVENING FACTOR - Junaedi, Junaedi; Supriyantoro, Supriyantoro; Mustikawati, Intan Silviana; Joyo, Ericko Ongko (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2024)
Incomplete medical record filling by doctors is still a widespread problem encountered in various hospitals. Incomplete medical record documentation is very detrimental to the hospital. This research aims to determine the correlation between motivation and workload on doctors' completeness of medical record filling through attitude mediation. This study was conducted with a cross-sectional design, which included 40 doctors who worked at the inpatient ward of Annisa Citeureup Hospital as the respondents. Motivation, knowledge, and attitudes were assessed using a questionnaire with a Likert scale, while the medical records completeness data was obtained by directly evaluating the medical records. Partial least squares (PLS) path analysis was done to analyze the association among the observed variables. Motivation, knowledge, and attitudes significantly influence the completeness of medical records. Motivation and knowledge do not directly correlate to the completeness of medical records but have a significant correlation mediated by attitude. Attitude is the factor that most influences the medical record completeness. Increasing the completeness of medical records would be directly influenced by increasing the positive attitude of doctors. Motivation and knowledge do not directly affect the completeness of medical records but affect attitude improvement.